Еволюція фінансового забезпечення соціального захисту населення - Чугунов, Ігор; Насібова, Ольга Вікторівна (Київський національний торговельно-економічний університет, 2020)
Розкрито передумови виникнення фінансового забезпечення соціального захисту населення. Визначено особливості становлення соціального захисту населення як системи фінансових відносин та інструменту стимулювання розвитку головної продуктивної сили суспільства. Здійснено аналіз фінансового забезпечення соціальних видатків у середині ХІХ та на початку ХХ ст. Виявлено основні чинники впливу на рівень соціального захисту населення та розвиток фундаментальних підвалин функціонування фінансового забезпечення зазначеної сфери.

Background. An improving the quality of social protection of the population should be accompanied by effective changes in the country’s financial policy, improving the mechanisms of public administration of socio-economic development of society. At present, it is necessary to deepen the theoretical foundations of financial security of social protection, taking into account the relevant historical experience, which will strengthen the impact of financial regulation on social development in the country. The aim of the article is to disclosure of preconditions of the origin and features of formation of the financial maintenance of social protection of the population. Materials and methods. The dialectical, historical and structural methods were used in the work to reveal the preconditions of the origin and characteristics of the peculiarities of the system formation of financial provision of social protection of the population; methods of analysis, synthesis, factor were used to determine the directions of development of mechanisms for financing social benefits. Results. The preconditions for the emergence of financial support for population social protection of the have been revealed. The peculiarities of the formation of social protection of the population as a system of financial relations and a tool to stimulate the development of the main productive force of society have been determined. The analysis of the financial security of social expenditures in the mid-nineteenth and early twentieth centuries has been carried out. The main factors influencing the level of social protection of the population and the development of the fundamental foundations of the financial support of this area have been identified. Conclusion. The tribal form of protection of individuals and charity, which have functioned for centuries, are gradually being replaced by state support and the development of private social assistance. Industrialization, migration, demographic changes have become the main prerequisites for the creation of centralized mechanisms for regulating social protection. Gradually, various forms, methods, techniques, tools of financial support of social protection of the population appear, which are transformed in accordance with the requirements of social development, accompanied by the creation of an appropriate financial mechanism.
Еvolution of financial support of the social protection of the population
Keywords: фінансове забезпечення; соціальний захист; соціальна допомога; соціальна підтримка; соціальні виплати; державні видатки; financial security; social protection; social assistance; social support; social benefits; government spending